Lower-Limb Amputees Adjust Quiet Stance in Response to Manipulations of Plantar Sensation - Shell, Courtney E.; Christie, Breanne P.; Marasco, Paul D.; Charkhkar, Hamid; Triolo, Ronald J. (Frontiers in Neuroscience, 2021)
Interfering with or temporarily eliminating foot-sole tactile sensations causes postural adjustments. Furthermore, individuals with impaired or missing foot-sole sensation, such as lower-limb amputees, exhibit greater postural instability than those with intact sensation. Our group has developed a method of providing tactile feedback sensations projected to the missing foot of lower-limb amputees via electrical peripheral nerve stimulation using implanted nerve cuff electrodes (PNS). As a step toward effective implementation of the system in rehabilitation and everyday use, we compared postural adjustments made in response to tactile sensations on the missing foot elicited by our system, vibration on the intact foot-sole, and a control condition in which no additional sensory input was applied. Three transtibial amputees with at least a year of experience with tactile sensations provided by our PNS system participated in the study. Participants stood quietly with their eyes closed on their everyday prosthesis while electrically elicited, vibratory, or no additional sensory input was administered for 20s. Early and steady-state postural adjustments were quantified by center of pressure location, path length, and average angle over the course of each trial. Electrically elicited tactile sensations and vibration both caused shifts in center of pressure location compared to the control condition. Initial (first 3s) shifts in center of pressure location with electrically elicited or vibratory sensory inputs often differed from shifts measured over the full 20s trial. Over the full trial, participants generally shifted towards the foot receiving additional sensory input, regardless of stimulation type. Similarities between responses to electrically elicited tactile sensations projected to the missing foot and responses to vibration in analogous regions on the intact foot suggest that the motor control system treats electrically elicited tactile inputs similarly to native tactile inputs. The ability of electrically elicited tactile inputs to cause postural adjustments suggests that these inputs are incorporated into sensorimotor control, despite arising from artificial nerve stimulation. These results are encouraging for application of neural stimulation in restoring missing sensory feedback after limb loss and suggest PNS could provide an alternate method to perturb foot-sole tactile information for investigating integration of tactile feedback with other sensory modalities.